If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + 3) = (x + 7)(x + -4) Reorder the terms: (2 + x)(x + 3) = (x + 7)(x + -4) Reorder the terms: (2 + x)(3 + x) = (x + 7)(x + -4) Multiply (2 + x) * (3 + x) (2(3 + x) + x(3 + x)) = (x + 7)(x + -4) ((3 * 2 + x * 2) + x(3 + x)) = (x + 7)(x + -4) ((6 + 2x) + x(3 + x)) = (x + 7)(x + -4) (6 + 2x + (3 * x + x * x)) = (x + 7)(x + -4) (6 + 2x + (3x + x2)) = (x + 7)(x + -4) Combine like terms: 2x + 3x = 5x (6 + 5x + x2) = (x + 7)(x + -4) Reorder the terms: 6 + 5x + x2 = (7 + x)(x + -4) Reorder the terms: 6 + 5x + x2 = (7 + x)(-4 + x) Multiply (7 + x) * (-4 + x) 6 + 5x + x2 = (7(-4 + x) + x(-4 + x)) 6 + 5x + x2 = ((-4 * 7 + x * 7) + x(-4 + x)) 6 + 5x + x2 = ((-28 + 7x) + x(-4 + x)) 6 + 5x + x2 = (-28 + 7x + (-4 * x + x * x)) 6 + 5x + x2 = (-28 + 7x + (-4x + x2)) Combine like terms: 7x + -4x = 3x 6 + 5x + x2 = (-28 + 3x + x2) Add '-1x2' to each side of the equation. 6 + 5x + x2 + -1x2 = -28 + 3x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 6 + 5x + 0 = -28 + 3x + x2 + -1x2 6 + 5x = -28 + 3x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 6 + 5x = -28 + 3x + 0 6 + 5x = -28 + 3x Solving 6 + 5x = -28 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 5x + -3x = -28 + 3x + -3x Combine like terms: 5x + -3x = 2x 6 + 2x = -28 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + 2x = -28 + 0 6 + 2x = -28 Add '-6' to each side of the equation. 6 + -6 + 2x = -28 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = -28 + -6 2x = -28 + -6 Combine like terms: -28 + -6 = -34 2x = -34 Divide each side by '2'. x = -17 Simplifying x = -17
| -5X-7y=-70 | | 3(t+2)+4(t-1)=72 | | 16+6z=-8 | | 3log^7x=9 | | -25y^2-60y+60= | | d/33 | | -109/3 | | F(x)=4x^2-24x+20 | | t/4-7=16 | | 6x+7=-48-5x | | x^2-2.8x=9 | | 3s-15=-15 | | 5x^2-9x-7=0 | | x/4=21/36 | | -8+5t=-6 | | 7+91x=52x+16 | | 40-2x=8-10x | | 1/2/5/4 | | 8m+6=28 | | 3x+100=8x-5 | | -4(2t+10)=-8 | | x^2+10x-25=3x+5 | | -10(s+4)=-111 | | 6x^4-216=0 | | -4(3x+9)=-12x+36 | | 5-4X=1/2 | | 12-2y(y)=10 | | 3(f-9)=-42 | | 5+7x(9-2)+14= | | xsquared-2.8x=9 | | 1/2(2a-4b | | 4+30x=20x+20 |